Income Analysis of Closed House Broiler Farm with Partnership Business Model - siswanto imam santoso; Teysar Adi Sarjana; Agus Setiadi (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This research aims to determine the performance and income of a closed-house broiler farm with partnership business model. The research was conducted in a closed broiler house owned by Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang, and in a partnership with Cemerlang Unggas Lestari Ltd. A total of 11,000 broilers were raised for each raising period in the closed broiler house. A case study method was used for this research. The data were collected using survey method; the primary data were collected directly through interviews with the farm operators and field observation. Secondary data were collected through data recording which includes production cost and obtained revenue in each raising period. The collected data were then analyzed through quantitative-descriptive study. A total 7 raising periods of production cost, revenue, and income in a year were analyzed. The results of this study showed that the average performances of closed-house broiler farm yield 0.37% depletion, 1.49 FCR, and 398.46 PI. The economic indicators showed that the average production cost was Rp292,668,800.00; which generated Rp327,300,779.00 revenue, Rp34,631,978.00 income, Rp183.055.535.00 NPV, and 1.24 BCR. The study concluded that the closed-house broiler farm generates higher income compared with the open house system.